The elegant universe : superstrings, hidden dimensions, and the quest for the ultimate theory - Greene, B. (Brian), 1963-; Rogers D. Spotswood Collection (1999)
Physicist Brian Greene relates the scientific story behind the research on string theory, which reveals a vision of the universe with new dimensions hidden within the fabric of space, black holes transmuting into elementary particles, rips and punctures in the space-time continuum, and gigantic universes interchangeable with minuscule ones
pt. 1. The edge of knowledge -- Tied up with string -- pt. 2. The dilemma of space, time, and the quanta -- Space, time, and the eye of the beholder -- Of warps and ripples -- Microscopic weirdness -- The need for a new theory : general relativity vs. quantum mechanics -- pt. 3. The cosmic symphony -- Nothing but music : the essentials of superstring theory -- The "super" in superstrings -- More dimensions than meet the eye -- The smoking gun : experimental signatures -- pt. 4. String theory and the fabric of spacetime -- Quantum geometry -- Tearing the fabric of space -- Beyond strings : in search of m-theory -- Black holes : a string/m-theory perspective -- Reflections on cosmology -- pt. 5. Unification in the twenty-first century -- Prospects
Includes bibliographical references (pages 427-428) and index
Keywords: Superstring theories -- Popular works; Cosmology -- Popular works; Popular works